@Utkarsh, this theorem is applicable only when λ is not in our language.. So our grammar will be S - - - > λ | aBb | b ; B - - - > b ... Now, in the given explanation, variable B should also be nullable.. Because B is generating all the variables which are already nullable.. So, B should also be included in the set of nullable variables.. Bcoz nullable means which can generate λ..

Now, for the last statement consider the following grammar :-

S - - - > aA

A - - - > BC

B - - - > b | λ

C - - - - > c | λ

Since B and C are nullable.. So A will also be nullable.. So, here all Xi are nullable.. So, A----> λ will not be included in the new grammar according to rule.. So new production set will be S - - - > a | aA

A - - - > B | C | BC

B - - - > b

C - - - - > c